(untitled) (Global Journals of Research in Engineering, 2012)
In the proposed research is produced and tested performance of electromagnetic fuel saver. Purpose of the considered work is to research effect of varying of core of electromagnetic fuel saver to the performance of the internal combustion diesel engine. Materials for core of electromagnetic fuel saver are made of plain steel and copper. Diameters of the wire winding, which is used in the research, are 0.25 mm and 0.35 mm. Speed of the engine, and number of coil which is coiled in the winding core of the fuel saver are chosen as the testing variables. The produced fuel saver is tested in the laboratory and on the road in the traffic jam condition and in the highway. Measured variables in the laboratory is specific fuel consumption, but measured variable for road testing is fuel consumption. From this research is obtained that the performance of the electromagnetic fuel saver which use copper core is better than the electromagnetic fue